Construction of desirable NiCo2S4 nanotube arrays on nickel foam substrate for pseudocapacitors with enhanced performance. (1st January 2015) - Cai, Daoping; Wang, Dandan; Wang, Chenxia; Liu, Bin; Wang, Lingling; Liu, Yuan; Li, Qiuhong; Wang, Taihong
Graphical abstract: The NiCo2 S4 nanotube arrays (NTAs) grown on nickel foam substrate exhibits excellent electrochemical performance for high-performance supercapacitors. Highlights: The NiCo2 S4 NTAs grown on nickel foam have been synthesized through a facile two-step hydrothermal method. The NiCo2 S4 NTA electrode exhibits excellent performance for supercapacitors. This work highlights the importance of synthesis of nanotubular morphology for supercapacitors. Abstract: Ternary NiCo2 O4 synthesized via annealing NiCo-precursor has been extensively studied as an advanced electrode material for high-performance supercapacitors. In this work, we demonstrate a facile hydrothermal synthesis of NiCo2 S4 nanotube arrays (NTAs) by simply treating the NiCo-precursor with Na2 S solution based on the Kirkendall effect. The NiCo2 S4 NTAs grown on nickel foam substrate are directly evaluated as binder-free electrode for supercapacitors. Impressively, the NiCo2 S4 NTA electrode delivers an ultrahigh capacitance of 15.58 F cm −2 at a current density of 10 mA cm −2, which is much higher than 3.63 F cm −2 of the mesoporous NiCo2 O4 nanowire array (NWA) electrode. In addition, the NiCo2 S4 NTA electrode also exhibits good cycling stability with 79.3% capacitance retention at high current density of 60 mA cm −2 after 2000 cycles. In view of the excellent electrochemical performance and the facile and cost-effective synthesis, such NiCo2 S4 NTA electrode would hold great promise for high-performance supercapacitor applications in future.